KEPERCAYAAN DAN KETERBUKAAN PADA PERSAHABATAN DI MASA EMERGING ADULTHOOD: MODERASI KECEMASAN SOSIAL - Gabriella Shalisha; Yohanes Budiarto (PAEDAGOGY : Jurnal Ilmu Pendidikan dan Psikologi, 2026)
Close friendships are interpersonal relationships generally grounded in trust and self-disclosure. However, not all individuals are able to engage in self-disclosure optimally. Social anxiety, defined by fears of negative evaluation, may hinder disclosure. Yet studies examining its moderating role between trust and self-disclosure among emerging adults in Indonesia remain limited. This study aimed to investigate the effect of trust on self-disclosure in close friendships among emerging adults and examine whether social anxiety moderates this relationship. A quantitative correlational design with moderation regression analysis was employed involving 383 participants (91 males and 292 females) aged 18–25 years recruited through convenience sampling. Trust was measured using the 14-item Trust Scale (α = .855), self-disclosure using the 10-item Self-Disclosure Index (α = .851), and social anxiety using two dimensions of the Social Anxiety Scale for Adolescents with 10 items (α = .902). Analysis was conducted using the MedMod module in Jamovi. The results indicated that trust positively and significantly predicted self-disclosure (b = .5009, p < .001), whereas social anxiety did not moderate the relationship (b = -.0107, p = .789). These findings highlight the crucial role of trust in fostering self-disclosure in close friendships and suggest that social anxiety does not necessarily alter this dynamic among emerging adults.